2010
DOI: 10.3346/jkms.2010.25.8.1128
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Foodborne Norovirus Outbreak in Incheon, Korea

Abstract: On June 14, 2008, an outbreak of gastroenteritis occurred among elementary school students in Incheon. We conducted an investigation to identify the source and described the extent of the outbreak. We performed a retrospective cohort study among students, teachers and food handlers exposed to canteen food in the elementary school. Using self-administered questionnaires we collected information on symptoms, days of canteen food eaten, food items consumed. Stool samples were collected from 131 symptomatic people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Food poisoning cases continue to arise [32]; therefore, preventative measures should be taken against NoV contamination of groundwater. Although this study examined NoV contamination of drinking water, further studies are required to investigate enteric virus contamination of food.…”
Section: Discussionmentioning
confidence: 99%
“…Food poisoning cases continue to arise [32]; therefore, preventative measures should be taken against NoV contamination of groundwater. Although this study examined NoV contamination of drinking water, further studies are required to investigate enteric virus contamination of food.…”
Section: Discussionmentioning
confidence: 99%
“…2010 yılında İngiltere'de geçmişe yönelik taranan örneklerde %4.5 oranında norovirüs belirlemişlerdir (34) . Çin, Kore ve Tayvan gibi Asya ülkelerinde 2005-2009 yılları arasında yapılan çalışmalarda %13.1-45 oranında norovirüs pozitifliğini göstermişlerdir (36)(37) .…”
Section: Discussionunclassified
“…2 The virus can be excreted in the absence of symptoms, 7 so improper manipulation by an asymptomatic food handler can lead to an outbreak. 8,9 On December 19, 2012, it was reported that 30 people from the university in Jimei District, Xiamen City, China had developed acute diarrhea and fever. Rectal swab samples from seven of the patients were found to be positive for NoV GII using reversetranscriptase PCR (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%